FRI0258 Validation of Bioelectrical Impedance Analysis for The Assessment of Body Composition in Patients with Systemic Sclerosis. (15th July 2016) - Spanjer, M.J.; Bultink, I.E.M.; de van der Schueren, M.A.E.; Voskuyl, A.E.
Abstract : Background: Malnutrition is a frequently reported complication in patients with systemic sclerosis (SSc) [1]. Especially low fat free mass (FFM) has been identified a prognostic factor for morbidity and mortality. Different methods are available to assess body composition. Bioelectrical impedance analysis (BIA) is a bedside method that has not yet been validated in this patient group. Objectives: To validate BIA against whole body dual-energy x-ray absorptiometry (DXA), for the assessment of body composition in patients with SSc. Methods: Body composition was assessed in 72 patients with whole body DXA (Hologic, Discovery A) and BIA (Bodystat Quadscan 400). The Geneva equation [2] was used to estimate FFM. The agreement between BIA and whole body DXA was assessed with Bland-Altman analysis and intraclass correlation coefficients (ICCs). The occurrence of malnutrition was assessed and defined as fat free mass index (FFMI) ≤14.5 kg/m 2 for women or ≤16.6 kg/m 2 for men [3]. Results: No difference was found between BIA and whole body DXA for the assessment of FFM as predicted by the Geneva equation (mean difference 0.02 ± 2.4 kg). ICC was 0.97 (95% CI: 0.95–0.98). The 95% limits of agreement, as assessed by Bland-Altman analysis were -4.6 kg and 4.6 kg. Despite normal BMIs (24.6 ± 4.3 kg/m 2 ), malnutrition was found in 14 (19.4%) patients with SSc. Conclusions: This study shows acceptable validity of BIA in determining FFM in patients with SSc on a group level, while on an individual level, FFM may vary by 4.6 kg. This study also demonstrated a high prevalence (19.4%) of malnutrition in patients with SSc, underlining the necessity of assessing body composition in this patient group. References: Harrison E, et al. Rheumatology. 2012;51:1747–56 Kyle UG, et al. Nutrition. 2001;17:248–53. Schutz Y, et al. Int J Obes Relat Metab Disord. 2002;26:953–60 Disclosure of Interest: None declared